WAYS OF DEVELOPING STUDENTS' TECHNOLOGICAL THINKING SKILLS - Mukhitdinova Jamilakhon Ruslanovna (American Journals, 2023)
The development of the ability to adapt to the innovations of the modern world, to actively participate in the processes of preparing the younger generation for the life of a constantly updating society and improving it in accordance with the requirements of the time is an important professional task of a teacher of a higher educational institution. This article discusses the development of students' thinking abilities with the help of creative technologies.
Keywords: Technology, creativity, education, upbringing mental abilities, teacher, educational institution.